In Vitro Study of Nitric Oxide Metabolites Effects on Human Hydatid of Echinococcus granulosus - Razika Zeghir-Bouteldja; Manel Amri; Saliha Aitaissa; Samia Bouaziz; Dalila Mezioug; Chafia Touil-Boukoffa (Journal of Parasitology Research)
Hydatidosis is characterized by the long-term coexistence of larva Echinococcus granulosus and its host without effective rejection. Previous studies demonstrated nitric oxide (NO) production (in vivo and in vitro) during hydatidosis. In this study, we investigated the direct in vitro effects of NO species: nitrite (NO2−), nitrate (NO3−) and peroxynitrite (ONOO−) on protoscolices (PSCs) viability and hydatid cyst layers integrity for 24 hours and 48 hours. Our results showed protoscolicidal activity of NO2− and ONOO− 24 hours and 3 hours after treatment with 320 μM and 80 μM respectively. Degenerative effects were observed on germinal and laminated layers. The comparison of the in vitro effects of NO species on the PSCs viability indicated that ONOO− is more cytotoxic than NO2−. In contrast, NO3− has no effect. These results suggest possible involvement of NO2− and ONOO− in antihydatic action and point the efficacy of these metabolites as scolicidal agents.